Is there a revival of patriarchal traditions in Kyrgyzstan? - Tugelbaeva, Bermeta G.; Aira D. Khamzaeva, Saule D. Khamzayeva, Altynai D. Khamzaeva,; Khamzaeva, Dzhamilia D. (Opción, 2019)
This article is devoted to factors responsible for the revival of discriminatory customs against women in Kyrgyzstan via several sociological methods and the in-depth interview as the leading research method. As results, the weakness of public administration, the lack of a positive ideology of change, ignorance of education problems, and the meeting moods among the rural and urban population, led to a surge in permissiveness among young people. In conclusion, Socialization plays a critical role in preserving gender inequality as a tool for reproducing and fixing the gender (social) roles of women and men.